Non-descent Vaginal Hysterectomy: Safety and Feasibility - Saha, R; Shrestha, NS; Thapa, M; Shrestha, J; Bajracharya, J; Padhye, SM (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: To assess safety and feasibility of non-descent vaginal hysterectomy. Methods: A hospital based prospective study was conducted at the department of obstetrics and gynecology of Kathmandu Medical College Teaching Hospital from 1st January 2010 to 31st December 2011. All the patients undergoing non -descent vaginal hysterectomy for benign indication, without suspected adnexal pathology were included in the study. Vaginal hysterectomy was done in usual manner. In bigger size uterus morcellation techniques like bisection, debulking, myomectomy, slicing, or combination of these were used to remove the uterus. Data regarding age, parity, uterine size ,estimated blood loss, length of operation, complication and hospital stay were recorded. Results: A total of 50 cases were selected for non-descent vaginal hysterectomy. Among them 43 cases successfully underwent non-descent vaginal hysterectomy. Commonest age group was (41-45 years) i.e. 40%. All patients were parous. Uterus size was <10 weeks in 27 cases and >10 weeks in 23 cases. Commonest indication was leiomyoma of uterus (63%). Mean duration of surgery was two hours. Mean blood loss was 205.26ml. Reasons for failure to perform NDVH was difficulty in opening pouch of Douglas in three cases. In rest of four cases there was difficulty in reaching the myoma and transverse diameter was too large so as to prevent descent of the uterus. The most common complication was post –operative pain in 23% of cases. Febrile morbidity was present in 4.6% of cases. Blood transfusion was required in seven cases. Average duration of hospital stay was three days. Conclusions: Vaginal hysterectomy for benign gynecological causes other than prolapse is safe and feasible. For successful outcome size of uterus, size in all dimensions and location of fibroid should be taken into consideration.Today in the era of minimally invasive surgery, non descent vaginal hysterectomy needs to be considered and seems to be a safe option. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11134 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 14-16